1985
DOI: 10.1152/jappl.1985.59.6.1815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic cigarette smoke exposure on pulmonary vasomotion in beagle dogs

Abstract: To study the effect of chronic cigarette smoke exposure on the resistive properties of the pulmonary vasculature, left lower lobes from 12 control beagles and 6 beagles who had smoked cigarettes (50 cigarettes/wk for 40 wk) were perfused in situ to measure the vascular pressure-flow relationship and the resistance of the three vascular segments with the arterial and venous occlusion technique. In control subjects the vascular resistance in the arterial, middle, and venous segments was 23, 36, and 41% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the site of vasocon striction with PGF2" was different than previously reported [6,12], the effects of serotonin, histamine and norepinephrine were similar in both studies. In another study we found that the effects of sero tonin were different in beagles than in mongrel dogs: In beagles, serotonin con stricted the pulmonary veins markedly [16], whereas, as demonstrated in the pres ent study (in mongrels), serotonin con stricted only the arteries. Thus in view of these different experimental results pro duced by the same investigator using the same techniques, it is reasonable to sug gest that contradiction in experimental re sults from different laboratories [2,6,12,17,18] on the effect of vasoactive sub stances in the same species as well as on different species are likely to be real rather than due to technical differences.…”
Section: Discussionmentioning
confidence: 74%
“…Although the site of vasocon striction with PGF2" was different than previously reported [6,12], the effects of serotonin, histamine and norepinephrine were similar in both studies. In another study we found that the effects of sero tonin were different in beagles than in mongrel dogs: In beagles, serotonin con stricted the pulmonary veins markedly [16], whereas, as demonstrated in the pres ent study (in mongrels), serotonin con stricted only the arteries. Thus in view of these different experimental results pro duced by the same investigator using the same techniques, it is reasonable to sug gest that contradiction in experimental re sults from different laboratories [2,6,12,17,18] on the effect of vasoactive sub stances in the same species as well as on different species are likely to be real rather than due to technical differences.…”
Section: Discussionmentioning
confidence: 74%
“…They found no effect at control pO?, but the smoke produced vasodilation during hypoxia. In contrast, Hakim et al [11] found that smoke reduced the basal vascular resistance but potentiated the hypoxic pres sor response.…”
Section: Discussionmentioning
confidence: 89%
“…In general, al though a bronchospastic response to cigarette smoke has been found [6][7][8], a possible linkage of the bron chospastic to a vasospastic response to cigarette smoke has not, to our knowledge, been investigated. A cardiovascular reaction is postulated because of cir culating mediators such as eicosanoids which are known to be altered by cigarette smoke inhalation [9], but investigations of this response have shown con flicting results [10][11][12], In this study, using the guinea pig model of cigarette smoke-associated emphysema, we were able to examine both the bronchospastic and vasospastic response to an acute exposure to cigarette smoke at the same time, and in the same animal. We could therefore examine the association of both of these effects with the inflammatory reaction produced by the smoke.…”
Section: Discussionmentioning
confidence: 99%